Autophagy: Playing an important role in diabetes and its complications - Ning Wang; Yinghua Zhou; Ebenezeri Erasto Ngowi; Aijun Qiao (Elsevier, 2024)
Diabetes, a chronic disease significantly affects peoples' health and quality of life. It is a major contributor of severe health complications, such as blindness, kidney failure, heart attacks, strokes, and lower limb amputations. Autophagy is a complex cellular process regulated by specific genes. It is responsible for degrading intracellular proteins and organelles within lysosomes, a process which is crucial for maintaining internal cellular balance and clearing damaged or obsolete cellular components. In the context of diabetes, autophagy plays a key role in maintaining blood glucose homeostasis, particularly through the regulation of insulin secretion and sensitivity. Additionally, autophagy aids in preserving the survival and function of pancreatic beta (β)-cells by eliminating harmful proteins within these cells, which is vital for the prevention and treatment of diabetes. Despite the key role autophagy plays in these aspects, its exact mechanisms and effects in diabetes are still complex and not fully understood. Therefore, further research is needed to deeply explore the specific mechanisms and potential therapeutic applications of autophagy in diabetes. This review explores autophagy's classification, mechanisms, role in diabetic pathogenesis and complications, and its potential in treatment strategies of disease.